The Role of Multicultural Education and Religious Moderation in Building an Anti-Violent Society - Anisa Oktaviana; Meyniar Albina (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Amidst cultural and religious diversity, the challenges of intolerance and violence based on differences are increasing. This study aims to analyze the role of multicultural education and religious moderation in creating a peaceful and anti-violent society. Using qualitative methods using library research, namely a method of collecting data by understanding and studying theories from various literatures related to the research. This study found that the integration of multicultural education in the school curriculum and the implementation of religious moderation programs in religious institutions significantly increased understanding and appreciation of diversity and reduced incidents of violence. This finding is in line with the theory that inclusive religious education and approaches can reduce the potential for conflict and strengthen social cohesion. This study recommends strengthening educational policies and government support for religious moderation programs to create a more tolerant and harmonious society.